Assessing the Antifungal Activity of a Soft Denture Liner Loaded with Titanium Oxide Nanoparticles (TiO2 NPs) - Amal Qasim Ahmed; Sattar Jabbar Abdul-Za; Dunya Malhan Hanweet; Julfikar Haider (MDPI AG, 2023)
Aim: Soft denture lining materials are susceptible to be colonized by different microorganisms, especially by Candida albicans (C. albicans), causing denture-induced stomatitis. This study was designed to evaluate the effectiveness of incorporating titanium dioxide nanoparticles (TiO2 NPs) into a soft denture liner towards reducing microbial activity. Method: A total of 40 PEMA-TiO2 nanocomposites samples were fabricated by adding 0.0 wt.% (control), 1.0 wt.%, 1.5 wt.%, and 2 wt.% TiO2 NPs to a heat cured soft denture lining material (polyethyl methacrylate, PEMA). The prepared samples were divided into four groups (n = 10) according to the content of TiO2 NPs. The uniformity of TiO2 NPS distribution within the denture liner matrix was assessed using a Scanning Electron Microscope (SEM). The viable count of C. albicans was evaluated to test the antifungal resistance of the developed composite. Results: The SEM images showed fairly homogeneous dispersion, with patches of TiO2 NPs agglomeration within the PEMA matrix and an increasing concentration of NPs with higher NP content. The particle map and EDX analysis confirmed the evidence of the TiO2 NPs. The mean viable count results for the control (0.0 wt.%) and 1.0 wt.%, 1.5 wt.%, and 2 wt.% TiO2 groups were 139.80, 12.00, 6.20, and 1.00, respectively, with a significant difference from the control group (p < 0.05). The antifungal activity also increased with the increase in the concentration of TiO2 NPs. Conclusions: The addition of TiO2 NPs into a heat-cured soft denture liner provided antifungal activity as evidenced by the reduced colonization of C. albicans. The antimicrobial activity of the liner material increased with the increased concentration of TiO2 NPS.